At odds with Europe: explaining populist radical right voting in Central and Eastern Europe. Issue 2 (2nd April 2020) - Santana, Andrés; Zagórski, Piotr; Rama, José
ABSTRACT: Focusing on six populist radical right parties from four Central and Eastern European countries, we show that the factors that account for the vote for these parties in Western Europe do not travel well to Central and Eastern Europe. Euroscepticism boosts populist radical right party voting almost without exception, while nativism, regarded as the most important factor in the West, is only relevant in about half of the cases. Moreover, economic deprivation has no impact in Central and Eastern Europe, and political mistrust works in the opposite way to the West.